2015
DOI: 10.1103/physrevb.92.174506
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of the superconducting energy gap in an intense microwave field

Abstract: We study photon assisted tunneling in Nb/AlOx/Nb Josephson junctions. A quantitative calibration of the microwave field in the junction allowed direct verification of the quantum efficiency of microwave photon detection by the junctions. We observe that voltages of photon assisted tunneling steps vary both with the microwave power and the tunneling current. However, this variation is not monotonous, but staircase-like. The phenomenon is caused by mutual locking of positive and negative step series. A similar l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Both sets of resonances were observed experimentally and described theoretically in (Boris and Krasnov, 2015). In that study, it was demonstrated that the Shapiro steps and PAT states originate from Cooper-pair and quasiparticle currents; and if a JJ is subjected to an intense microwave signal, both sets of resonances can be observed in the current, changing both the voltage and microwave power (Boris and Krasnov, 2015;Snyder et al, 2018).…”
Section: Multi-photon Transitions Meet Lzsm Theorymentioning
confidence: 86%
See 1 more Smart Citation
“…Both sets of resonances were observed experimentally and described theoretically in (Boris and Krasnov, 2015). In that study, it was demonstrated that the Shapiro steps and PAT states originate from Cooper-pair and quasiparticle currents; and if a JJ is subjected to an intense microwave signal, both sets of resonances can be observed in the current, changing both the voltage and microwave power (Boris and Krasnov, 2015;Snyder et al, 2018).…”
Section: Multi-photon Transitions Meet Lzsm Theorymentioning
confidence: 86%
“…The former relates to the tunneling of electrons (quasiparticles) and results in the steps on the current-voltage curve as displaced in voltage by k ω/e; the latter assumes the supercurrent response, which occurs as the Shapiro steps at voltages k ω/2e (Nakamura et al, 2001). Both sets of resonances were observed experimentally and described theoretically in (Boris and Krasnov, 2015). In that study, it was demonstrated that the Shapiro steps and PAT states originate from Cooper-pair and quasiparticle currents; and if a JJ is subjected to an intense microwave signal, both sets of resonances can be observed in the current, changing both the voltage and microwave power (Boris and Krasnov, 2015;Snyder et al, 2018).…”
Section: Multi-photon Transitions Meet Lzsm Theorymentioning
confidence: 96%
“…To visualize the effects of the periodic driving field [74], in Fig. 3, a contour plot of P -1 (t = 5/ω) is displayed as a function of (D, A z ), where the x-axis is the anisotropy D and the y-axis is the z-direction driving field amplitude A z .…”
Section: B Single-mode Phonon Coupling With Periodic Driving Fieldmentioning
confidence: 99%